(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
This study aimed to study the physicochemical properties and sensory acceptability of fish sausage incorporated with Dorado fish (Coryphaena hippurus). There are six different formulations with different ratios of surimi-to-Dorado fish, consisting of sample A (100:0), B (80:20), C (60:40), D (40:60), E (20:80) and F (0:100). Chemical properties include moisture (67.05-68.04%), ash (1.33-2.00%), fat (0.11-1.51%), protein (15.87-19.03%), and carbohydrate (10.40-14.64%) content, while texture profile analysis includes hardness (2426.0-2777.6 g), springiness (0.84-0.87 cm), cohesiveness (0.68-0.70), gumminess (1698.5-1876.5 g), and chewiness (1481.3-1698.5 g/cm). Colour profile, L*, a*, and b* was ranged from 80.56 to 82.17, -0.92 to 0.35, and 16.30 to 18.35, respectively. Sensory evaluation revealed no significant differences among samples, with sample B scoring the highest mean values in colour, tenderness, juiciness, and overall acceptability. The addition of Dorado fish percentage affects the physicochemical properties by increasing the fat, protein content, and a* value while decreasing the moisture, carbohydrate content, cohesiveness value, and L* value. Overall, incorporating Dorado fish into the sausage could contribute to cost reduction given its lower price compared to surimi and nutritional composition enhancement while maintaining a consistent preference level with the control sample.